Willingness to Utilize Cervical Cancer Screening Services Among, Antenatal Clinic Attendees in Selected Hospitals in Ibadan, Nigeria (2014)
"Introduction: Women of childbearing age who are sexually active are at risk of Cervical Cancer (CC), since they may have been exposed to Human Papilloma Virus. Majority of the women with invasive cervical cancer were never screened for this disease which is known to be a major cause of cancer deaths among women, especially in developing nations. This study sought to determine willingness to utilize Cervical Cancer Screening Services (CCSS) among Antenatal Clinic (ANC) attendees in Ibadan, Nigeria. Methods: This cross-sectional study was conducted in selected hospitals in Ibadan. Systematic random sampling was used to select 846 women attending ANC in the Hospitals. Data were collected from the respondents using validated structured questionnaire. Data were analysed using Statistical Package for Social Sciences (SPSS) and hypotheses were tested using Chi-square test at P≤0.05. Results: The women’s mean age was 27.9 ± 5.8 years. Majority, 94.8% were married, 49.1% had secondary school education and 64.2% were traders. Also, majority (68.0%) earned less than 10,000 naira/ month. Awareness of CC was quite low as 84.4% had never heard of cervical cancer while only 15.6% were aware of it. Over 73.6% of the women were willing to utilize CCS services but Uptake of CCS was 2.1%. Perceived hindrances to uptake were non-availability of CCS services, lack of information on CCS and cost of services among others. There was a significant association between awareness and willingness to utilize CCS services (P=0.000) as well as educational level and willingness to undergo screening (P =0.019). There was no significant association between age and willingness to utilize CCS services (P=0.834). Conclusion: There was high level of willingness but utilization of Cervical Cancer Screening Services was low among the women. There is need to provide more information on cervical cancer screening as well as make the services available at reduced cost.